2009
DOI: 10.1128/aac.01040-08
|View full text |Cite
|
Sign up to set email alerts
|

The Lipopeptide Antibiotic Friulimicin B Inhibits Cell Wall Biosynthesis through Complex Formation with Bactoprenol Phosphate

Abstract: Friulimicin B is a naturally occurring cyclic lipopeptide, produced by the actinomycete Actinoplanes friuliensis, with excellent activity against gram-positive pathogens, including multidrug-resistant strains. It consists of a macrocyclic decapeptide core and a lipid tail, interlinked by an exocyclic amino acid. Friulimicin is water soluble and amphiphilic, with an overall negative charge. Amphiphilicity is enhanced in the presence of Ca 2؉ , which is also indispensable for antimicrobial activity. Friulimicin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
157
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 44 publications
5
157
0
3
Order By: Relevance
“…The members of this group also share one action mechanism, which consists of binding and sequestering undecaprenol phosphate, a bacterial membrane constituent that is an essential carrier coenzyme in the assembly and membrane translocation of peptidoglycan precursors. This was shown first for amphomycin 28,29 and more recently for friulimycin 30 and laspartomycin. 31 Structural homology is greater within each group, yet it is also considerable between them (cf.…”
Section: Relationship To Other Calcium-dependent Lipopeptide Antibioticsmentioning
confidence: 81%
“…The members of this group also share one action mechanism, which consists of binding and sequestering undecaprenol phosphate, a bacterial membrane constituent that is an essential carrier coenzyme in the assembly and membrane translocation of peptidoglycan precursors. This was shown first for amphomycin 28,29 and more recently for friulimycin 30 and laspartomycin. 31 Structural homology is greater within each group, yet it is also considerable between them (cf.…”
Section: Relationship To Other Calcium-dependent Lipopeptide Antibioticsmentioning
confidence: 81%
“…At present, daptomycin is the only clinically used CDA, and its mode of action is the topic of ongoing investigation 6, 7, 8, 9. By comparison, the structurally similar CDAs laspartomycin C, friulimycin B, tsushimycin, and amphomycin have more clearly understood antibacterial mechanisms 10, 11, 12, 13, 14. It was recently reported that laspartomycin C forms a high‐affinity complex ( K d =7.3±3.8 n m ) with the bacterial cell wall precursor undecaprenyl phosphate (C 55 ‐P) and in doing so inhibits peptidoglycan biosynthesis, ultimately leading to cell death 14.…”
mentioning
confidence: 99%
“…19 The scenario is even more disappointing for compounds targeting Gram-negative pathogens, in which old drugs have been revamped for new uses, and none of them has reached phase III yet (Table 1). Ceftazidime is a marketed cephalosporin being developed in combination with NXL104, a representative of a new class of b-lactamase inhibitors, 20 which renders cephalosporin effective against most b-lactamase-producing enterobacteria.…”
mentioning
confidence: 99%